Effect of Salt Concentration and Fermentation Time In The Development of Anchovy (Stolephorus Sp) Bekasam as Tempura Raw Material - Ririn Margiati; Ilham Marvie; Syahrizal Nasution (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aimed to analyze the effect of salt concentration and fermentation time on the chemical characteristics and lactic acid bacteria of anchovy bekasam, and the sensory evaluation of anchovy bekasam as a raw material for tempura. Methodology: The tests conducted included water content (thermogravimetry), pH (pH meter), fat content (soxhlet), bacterial count (TPC), and sensory evaluation (hedonic). The study used a Randomized Complete Block Design (RCBD) with two factors: salt concentration (15% and 20%) and fermentation time (4 days and 7 days).Results: The results indicated that both salt concentration and fermentation time significantly affected the water content, pH, and total lactic acid bacteria. The fat content was not significantly affected by the two factors but showed a decrease. Findings: Variations in salt concentration and fermentation time influenced the panelists' sensory preferences for color, aroma, taste, texture, and overall acceptability. The highest overall liking score was achieved by the sample with 15% salt concentration and 7 days of fermentation (K1L2). Novelty: This research provides insight into the optimal conditions for producing anchovy bekasam with desirable chemical and sensory properties, specifically for its use as a raw material for tempura. Originality: The study highlights the impact of different salt concentrations and fermentation times on both the chemical and sensory characteristics of bekasam, offering new information on improving its production process. Conclusions: The sample with 15% salt concentration and 7 days fermentation time yielded the most favorable results in terms of both chemical characteristics and sensory evaluation. Paper Type: Experimental Research Article Keywords: Bekasam; fish; fermentation; salt; tempura